Analysis of the Accuracy of Diagnosis Codes Based on ICD-10 with the Application of the 4th Character at the Puskesmas of Semarang City - Munandziroh, Munandziroh; Asmorowati, Andri; Rahadiyanto , Cahyono; Prasetyowati, Asih (Universitas Muhammadiyah Sidoarjo, 2024)
The accuracy of the diagnosis code on the medical record document is used as a basis for making reports. If the diagnosis code is not properly coded then the resulting information will have low validation. The results of the initial survey at Puskesmas Genuk in the Top 10 of Disease in 2022, there are still many diagnosis codes that have not been coded until the 4th character. Objective is determine the accuracy analysis of disease diagnosis codes based on ICD-10 with the application of the 4th character of the fourth quarter at Puskesmas Genuk in 2022.This type of research is descriptive quantitative with a retrospective study approach. The primary data sources used are observation and interviews while the secondary data is from medical record data obtained from SIMPUS. The total population was 4,861 medical record data while the samples used were 98 with systematic random sampling techniques.Based on the results of research on 98 medical record data, the exact code is 21 (27.23%) while the incorrect code is 77 (72.77%). The inaccuracy of the diagnosis code is because the coding officer is not PMIK, the code is given only up to the 3rd character, there is no SOP for giving Disease Diagnosis Codes, not using ICD-10 but a list of SIMPUS codes. Conclusion are accuracy of the diagnosis code of 27.23% is much lower than the inaccuracy, coding officers from PMIK should be conducted, Training on Giving Disease / Action Coding, Diagnosis Codes at SIMPUS are given keys so that coders can choose a specific code, SIMPUS plus facilities for PMIK officers to validate coding after service